Patient Satisfaction in Pediatric Surgical Care: A Systematic Review. (26th March 2014) - Espinel, Alexandra G.; Shah, Rahul K.; McCormick, Michael E.; Krakovitz, Paul R.; Boss, Emily F.
Abstract : Objective: This study seeks to synthesize evidence‐based findings related to patient satisfaction as a process measure in pediatric surgical care. Data Sources: PubMed, CINAHL, Scopus, and the Cochrane Central Register of Controlled Trials. Review Methods: We queried 4 standard search engines (1992‐2013) for studies specific to pediatric surgical fields in which patient or parent satisfaction or experience of care was a primary outcome measure. Data were systematically analyzed to determine study characteristics, setting, parent or patient focus, measure of experience, and bias. Two independent investigators independently reviewed all articles. Results: The initial search yielded 4748 publications (1503 duplicates), of which 170 underwent full‐text review. Thirty‐five were included for analysis; the majority (24/35, 77%) were published in the last 5 years. Studies examined experience of the child (3/35), parent (23/35), or both (9/35). Experience and satisfaction were evaluated either by validated self‐assessment instruments (8), by satisfaction tools (8), or by nonstandard institutional or author‐developed tools (19). Experience was measured in the outpatient (7), preoperative (11), operative (14), and postoperative (3) care settings. Specific findings were unique to setting; however, in many studies higher satisfaction correlated with education/information giving, health care provider interpersonal behaviors, and facile/efficient care processes. Conclusion: The patient experience of care is a valuable quality measure that is being more frequently evaluated as a mechanism to improve pediatric surgical care processes. Findings related to patient satisfaction and experience of care may be limited due to lack of measurement using validated tools. Findings from this review may bear significance as patient experience measures become routinely integrated with quality and reimbursement.